PERBANDINGAN METODE SIMPLE QUEUES DAN QUEUES TREE UNTUK OPTIMASI MANAJEMEN BANDWIDTH JARINGAN KOMPUTER DI STMIK PPKIA PRADNYA PARAMITA MALANG - Syaifuddin, Aris; Yunus, Mahmud; Sundari, Retno (JURNAL TEKNOLOGI INFORMASI: Teori, Konsep, dan Implementasi, 2013)
This research resulted in a comparison between the Simple Queues method and Queues Tree using Mikrotik router that takes a case study in STMIK PPKIA PRADNYA PARAMITA MALANG has been tested to determine which method is the most optimal deal of bandwidth sharing on computer networks. After finding out where the most optimal method will be applied in STMIK PPKIA PRADNYA PARAMITA MALANG to maximize network performance and bandwidth sharing in place, the results of the study lead to the conclusion that it is the Simple Queues more optimal than the Queues Tree.The Internet use in massive resulting in reduced network performance with increasing network users. Way that can be taken to reduce the decrease in network performance is to perform bandwidth management. Bandwidth management is very important in setting the bandwidth allocation will be given to the user to avoid the seizure of bandwidth allocation on the network.The research method used is the Simple Queues and Queues Tree method. Both of these methods will be made to determine the results of a comparison with one of the methods Simple Queues and Queues Tree is quite optimal. Key words: Mikrotik, Simple Queues, Queues Tree, Bandwidth